Emotional intelligence and self-concept in school students of Lima - Matalinares Calvet, María Luisa (2005)
The main objective of this research was to establish if it existed or no relationship between Emotional Intelligence and Self-concept on high school students from Metropolitan Lima. For this effect, at the beginning, it is tested to 601 high school students, female, and male, with ages between 15 and 18 years old, they were studying at the 5th grade of High School, and they had came from eight state educational institutions from Metropolitan Lima to whom were tested with Emotional Intelligence Inventory proposed by Bar On and Selfconcept Assessment test, proposed by Musitu, García & Gutiérrez. The exclusion criterion for two tests determined a final sample of 203 High School students. The results showed a positive correlation between Emotional Intelligence and Self-concept, a relationship between Emotional Intelligence and Social and Emotional clusters of Self-concept was found too. Besides, there were positive relationships between Self-concept with Emotional Self Selfawareness, and Self concept with Emotional Quotient of Emotional Intelligence Inventory For the purpose of analysis, Self-concept of mens and women was compared, indicating significative differences on Academic Cluster for women and Emotional Cluster for men. Finally, responses from men and women on Emotional Intelligence, reflected significative differences for women on Interpersonal Emotional Quotient of Emotional Intelligence inventory.